“I Should Have Died, but Suicide Can Never Be an Option”: A Longitudinal Narrative Analysis of a Relational Complex Trauma Victim Surviving during His Emerging Adult - Amalia Rahmandani; M. A. Subandi; Muhana Sofiati Utami (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Existing studies examining relational complex trauma in emerging adults are mostly associated with adverse effects, whereas recovery may be difficult let alone growth—it is doubted. Thus, this study aimed to understand how a relational complex trauma victim survived in his emerging adulthood. A case study with longitudinal narrative analysis explored the accounts of a qualified participant, particularly those midst close contact with perpetrators that still maintained their former caregiving style. A 20-year-old male typed his story while having anxiety and depressive symptoms. He was interviewed at the age of 24 when finally living without any symptoms of clinical disorders as well as gaining some actualizations. The analysis focused on how he described his experiences and what he talked about. Two types of narrative forms were identified in each data collection: 'All included in my typed stories but negatives’ and ‘My tone stories are more diverse, but the fluency is lacking’. There were five narrative themes concluded, namely living with conditioned destructive ways of nurturing, enduring the negative consequences of ongoing parent-related conflicts, distancing without escaping and gaining self-actualizations gradually, benefiting from external social supports while regulating self to approach problems carefully, and framing the future as certain and uncertain. The findings indicate that individual affected by relational complex trauma may empower and maintain his personal, or interpersonal resources although from outside own family. Focusing on gradually encouraging potentials but also being sensitive to the flexibility of coping and the available social support, may have good impacts on recovery.